Investigation of enhanced particle swarm optimization algorithm for the OFDMA interference management in heterogeneous network - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hashim, Wahidah; Islam, Shayla (Science & Engineering Research Support Society, 2016)
In orthogonal frequency division multiplexing Access (OFDMA) systems resource allocation to the subcarrier is essential owing to the insufficient resources available at the base station. In OFDMA, subcarrier and power allocation are not separate; thereby this two allocation are not self-governing. This paper proposes the subcarrier allocation approach through investigating previous methods, and also the Enhanced Particle Swarm Optimization (PSO) algorithm is analyzed. The both of the algorithms cross functionality is analyzed and compared the performance of the subcarrier allocation of OFDMA systems in Heterogeneous Network (HetNet). The simulation results show that the PSO approach efficiently allocates the OFDMA subcarriers.